2018
DOI: 10.1038/s41598-018-29196-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endothelin 1 in Remote Preconditioning-Induced Cardioprotection through connexin 43 and Akt/GSK-3β Signaling Pathway

Abstract: The present study was aimed to explore the role of endothelins in remote preconditioning (RP)-induced myocardial protection in ischemia-reperfusion (IR) injury. RP stimulus was given by subjecting hind limb to four cycles of ischemia and reperfuion (5 minutes each) using blood pressure cuff in male rats. Following RP, hearts were isolated and subjected to 30 minutes of ischemia and 120 minutes of reperfusion on Langendorff apparatus. The extent of myocardial injury was determined by measuring the levels of LDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Experimental studies have indicated that intervention and ischemia preconditioning using some pharmacological agents can recruit the PI3K/Akt pathway and confer powerful cardioprotection [13]. It has been proposed that pharmacological targeting of the Akt pathway may potentially diminish ischemia reperfusion (IR) injury [14].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have indicated that intervention and ischemia preconditioning using some pharmacological agents can recruit the PI3K/Akt pathway and confer powerful cardioprotection [13]. It has been proposed that pharmacological targeting of the Akt pathway may potentially diminish ischemia reperfusion (IR) injury [14].…”
Section: Introductionmentioning
confidence: 99%
“…The total protein content in the homogenate solution was measured by Lowery's method in which 100 µl of sample was mixed with 1 ml of color complex forming compound (sodium potassium tartrate, copper sulfate, Folin-Ciocalteau reagent) to yield a color, whose OD was measured at 750 nm. The apoptotic markers (bcl-2 and caspase 3) were represented with respect to total protein content [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…These results were later confirmed by Duda et al [ 93 ] . Recently, endogenous endothelin-1 and ET A receptor were found to be involved in the cardioprotective effect of remote preconditioning in rats [ 94 ] . However, there is little evidence that the selective ET A receptor antagonist BQ123 may increase cardiac tolerance to reperfusion in rabbits [ 95 ] .…”
Section: The Mechanism Of the Myocardial Ischemic Tolerance Elicited ...mentioning
confidence: 99%